Octreotide plus IBI-318 plus anlotinib in the treatment of multiple neuroendocrine metastases of unknown primary lesions: a case report - Qin, Haoyue; Yan, Huan; Zhang, Xing; Huang, Zhe; Chen, Yangqian; Zhang, Yuda; Xiang, Siqi; Zhang, Yongchang; Yang, Nong; Zeng, Liang (Frontiers in Oncology, 2024)
BackgroundThe second-line treatment of neuroendocrine tumors (NETs) of unknown primary origin remains uncertain. This report presented a patient who received octreotide plus IBI-318 plus anlotinib as a second-line treatment for multiple metastatic NETs of unknown primary lesions after the failure of octreotide plus everolimus.Case presentationA 32-year-old male patient presented with elevated CEA (197.83 ng/ml) without specific symptoms. A contrast-enhanced computed tomography (CT) scan showed multiple metastatic lymph nodes and multiple low-density nodules in the liver of undetermined nature. A right supraclavicular lymph node biopsy indicated NET, but the primary tumor origin remained unknown. PD-L1 expression was negative in tumor tissue according to immunohistochemistry. Immunofluorescence indicated the CD4+ T cells, CD8+ T cells, and Treg cells were gathered around blood vessels, with only a few infiltrating lymphocytes in the tumor tissue. Treatment with octreotide (30 mg/28 d) plus everolimus (5 mg qd) led to disease progression after three cycles. Treatment was changed to octreotide (30 mg/28 d) plus IBI318 (400 mg/28 d) plus anlotinib (10 mg/1-14 d/q3w), leading to partial remission, which was sustained up to the last follow-up (June 20, 2023), with a PFS of 11 months. The patient experienced no treatment-related adverse reactions.ConclusionsOctreotide plus IBI318 plus anlotinib achieved benefits in a patient with advanced NETs of unknown primary lesions after first-line treatment failure, even though with low PD-L1 expression. This case suggests that combining SSAs, TKIs and PD-1/PD-L1 inhibitors could be an alternative second-line treatment for patients with advanced, well-differentiated NETs.